Application of Transparent Coffee Steamer Machine for Coffee Beverage Processing Small Business: Aplikasi Mesin Kopi Bening Sistem Uap Untuk Usaha Kecil Pengolahan Minuman Kopi - Megandhi Gusti Wardhana; Adi Pratama Putra; Charis Fathul Hadi (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
Coffee is a fairly large plantation commodity in Indonesia. Coffee drinks are a coffee variant product that is in great demand by the public. The process of making coffee drinks can be optimized with the application of technology. The purpose of writing this article is to describe the application of a clear coffee machine with a steam distillation system that can be utilized by the small business sector of coffee beverage processing. Clear coffee is an innovation resulting from a patented research by lecturers so that it can be developed into a coffee beverage production tool. Making clear coffee uses the principle of steam distillation using a tube-shaped device with stainless steel material. The distillation process is optimized by using a 15 watt electric aerator. Heating is done with an LPG-fueled heater. The application of technology is carried out with the stages of design, tool making and tool testing. The trial was carried out by processing 1 kg of coffee powder with 500 ml of water. The results of the trial showed that the process time was 25 minutes with relatively small consumption of electricity and LPG fuel. This clear coffee machine has the potential to be applied in the production of coffee drinks.